A taxonomic study on the genus Prionyx Vander Linden, 1827 (Hymenoptera: Sphecidae: Prionychini). Subgenus Harpactopus F. Smith, 1856 - Danilov, Yuriy N.; Odintsev, Oleg A.; Kobets, Anastasia S. (Zootaxa, 2024)
The original keys to the species of subgenus Harpactopus F. Smith, 1856 are provided. The following new synonymy has been established: Prionyx globosus (F. Smith, 1856) (=Harpactopus australis de Saussure, 1867), Prionyx radoszkowskyi (Kohl, 1888) (=Sphex guichardi de Beaumont, 1967), Prionyx stschurowskii (Radoszkowski, 1877) (=Sphex sirdariensis Radoszkowski, 1877), and Prionyx subfuscatus (Dahlbom, 1845) (=Prionyx binghami Jha et Farooqi, 1996). Prionyx crudelis (F. Smith) is newly recorded from Afghanistan and Uzbekistan, P. funebris (Berland) from Yemen, P. macula (Fabricius) from Turkey, P. melanotus (F. Morawitz) from Kazakhstan and Uzbekistan, P. persicus (Mocsáry) from Afghanistan, and P. subfuscatus (Dahlbom) from Azerbaijan. The type localities of Sphex stschurowskii Radoszkowski and S. sirdariensis Radoszkowski are updated and corrected.